Validation of established thyroid ultrasound volume norms in a Chernobyl cohort - Lydia B Zablotska; Robert J McConnell; Aleksandr V Rozhko; Patrick O'Kane; Vasilina Yauseyenka; Mark P Little; Victor Minenko; Vladimir Drozdovitch; Tamara Moskvicheva; Maureen Hatch; Tamara Yeudachkova; Kiyohiko Mabuchi; et al. (European Thyroid Journal, 2025)
Objective: To establish thyroid ultrasound volume norms appropriate for studies of diffuse goiter in a cohort of children and adolescents from an iodine-deficient population exposed to 131I by the Chernobyl fallout. Methods: A cohort of 11,970 Belarusians aged ≤18 years at the time of the 1986 Chernobyl accident with individual thyroid radiation dose estimates was screened 10–18 years later. From these, a low-dose subset of 2,392 with no thyroid diseases was selected to construct age- and sex-specific normative values for thyroid ultrasound volume, compared to Belarusian Ministry of Health (MOH) norms and existing WHO and European standards. Results: Cohort-specific values were generally lower than MOH norms and WHO standards for 11–17-year-olds. For those aged ≥18 years, internal norms were 30% higher in males and 15–30% lower in females than MOH norms, and exceeded European values for both sexes. Thyroid volume norms were about 40% higher in males and 30% higher in females as a function of BSA compared to European values. Thyroid volume continued to increase in both sexes, and by age 30–34 years, cohort-specific norms were 6% higher in males and 26% higher in females than European values. Urinary iodine concentration did not significantly explain variance in thyroid volume beyond sex, age, and BSA. Conclusions: In this iodine-deficient cohort of young Belarusians exposed to 131I by Chernobyl fallout, thyroid ultrasound volumes differed substantially from MOH norms and established WHO standards, prompting a revision of diffuse goiter definition using cohort-specific normative values.